Impact of FTO genotypes on BMI and weight in polycystic ovary syndrome: a systematic review and meta-analysis. - Wojciechowski, P; Lipowska, A; Rys, P; Ewens, K; Franks, S; Tan, S; Lerchbaum, E; Vcelak, J; Attaoua, R; Straczkowski, M; Azziz, R; Barber, T; et al. (2012)
AIMS/HYPOTHESIS: FTO gene single nucleotide polymorphisms (SNPs) have been shown to be associated with obesity-related traits and type 2 diabetes. Several small studies have suggested a greater than expected effect of the FTO rs9939609 SNP on weight in polycystic ovary syndrome (PCOS). We therefore aimed to examine the impact of FTO genotype on BMI and weight in PCOS. METHODS: A systematic search of medical databases (PubMed, EMBASE and Cochrane CENTRAL) was conducted up to the end of April 2011. Seven studies describing eight distinct PCOS cohorts were retrieved; seven were genotyped for SNP rs9939609 and one for SNP rs1421085. The per allele effect on BMI and body weight increase was calculated and subjected to meta-analysis. RESULTS: A total of 2,548 women with PCOS were included in the study; 762 were TT homozygotes, 1,253 had an AT/CT genotype, and 533 were AA/CC homozygotes. Each additional copy of the effect allele (A/C) increased the BMI by a mean of 0.19 z score units (95% CI 0.13, 0.24; p = 2.26 × 10(-11)) and body weight by a mean of 0.20 z score units (95% CI 0.14, 0.26; p = 1.02 × 10(-10)). This translated into an approximately 3.3 kg/m(2) increase in BMI and an approximately 9.6 kg gain in body weight between TT and AA/CC homozygotes. The association between FTO genotypes and BMI was stronger in the cohorts with PCOS than in the general female populations from large genome-wide association studies. Deviation from an additive genetic model was observed in heavier populations. CONCLUSIONS/INTERPRETATION: The effect of FTO SNPs on obesity-related traits in PCOS seems to be more than two times greater than the effect found in large population-based studies. This suggests an interaction between FTO and the metabolic context or polygenic background of PCOS.